2017
DOI: 10.1186/s13075-017-1300-6
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed microcirculation in the hands of patients with systemic sclerosis detected by fluorescence optical imaging: a pilot study

Abstract: BackgroundUtilising fluorescence optical imaging (FOI), the distribution of an intravenously applied colouring agent indocyanine green (ICG) can be analysed with the potential to identify malperfusion by little to no tissue enhancement. Systemic sclerosis (SSc) is characterised by the presence of digital ulcers reflecting progressive vasculopathy.The objective was to investigate the potential of FOI in the detection of disturbed microcirculation in the hands and fingers of patients with SSc and to link FOI fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…The included SSc patients received clinical examination, nailfold capillaroscopy (NC), colour Doppler ultrasonography (CDUS) [8,9], and fluorescence optical imaging (FOI) [8,10] of both hands at baseline, and also their patient history was taken as described in detail in our previous publications [8][9][10]. The two examiners were not blinded to patient history or clinical manifestations of the disease when performing the imaging techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The included SSc patients received clinical examination, nailfold capillaroscopy (NC), colour Doppler ultrasonography (CDUS) [8,9], and fluorescence optical imaging (FOI) [8,10] of both hands at baseline, and also their patient history was taken as described in detail in our previous publications [8][9][10]. The two examiners were not blinded to patient history or clinical manifestations of the disease when performing the imaging techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been shown that FOI is able to visualize changes in joint inflammation during anti-rheumatic therapy [30,31] and that it can even detect subclinical synovitis in patients with inflammatory arthritis [32]. It was not only used in diagnostics and monitoring of RA and other arthritic diseases, but also for the detection of a disturbed microcirculation and prediction of digital ulcers in systemic sclerosis (SSc) [33,34]. Pfeil et al used FOI in SSc patients to detect inflammation of the soft tissue and monitor the effectiveness of treatment [35].…”
Section: Introductionmentioning
confidence: 99%
“…(28,30,(39)(40)(41) Following studies concentrated on the examination of OA with different in ammatory patterns (36) or decreased blood ow in systemic sclerosis. (33,34) To our knowledge, we are the rst group to investigate potential subclinical in ammation of the skin in Pso/PsA patients. Since skin in ammation, increased rate of vessel in ammation (42) and arterial stiffness (25) has been shown in patients with Pso/PsA, we hypothesized that ICG-based FOI would be a valuable method to visualize impaired microcirculation in Pso/PsA.…”
Section: Discussionmentioning
confidence: 99%